2022
DOI: 10.7759/cureus.27345
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID Syndrome and Severity of COVID-19: A Cross-Sectional Epidemiological Evaluation From North India

Abstract: BackgroundCOVID-19 has now lasted for more than two years as a pandemic and has had enduring effects on the health of people as the post-COVID syndrome. Recent literature has shown the long-term effects of COVID-19 on various organ systems, including but not limited to respiratory, cardiovascular, neurological, musculoskeletal, and gastrointestinal systems. Methods and objectivesWe aimed to estimate the prevalence of post-acute COVID symptoms in a tertiary care center in northern India; observe the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Fatigue was the most common symptom reported in post-COVID syndrome assessment, followed by post-exertion malaise and headache. Similar findings have been reported by Uniyal N et al and Anjana NK et al 16,17 A total of 29 participants reported fatigue and 5 post-COVID syndrome cases reported difficulty in breathing. A total of 8 participants in the post-COVID syndrome assessment reported difficulty in concentrating or thinking and mood changes.…”
Section: Discussionsupporting
confidence: 88%
“…Fatigue was the most common symptom reported in post-COVID syndrome assessment, followed by post-exertion malaise and headache. Similar findings have been reported by Uniyal N et al and Anjana NK et al 16,17 A total of 29 participants reported fatigue and 5 post-COVID syndrome cases reported difficulty in breathing. A total of 8 participants in the post-COVID syndrome assessment reported difficulty in concentrating or thinking and mood changes.…”
Section: Discussionsupporting
confidence: 88%
“…Via multivariate analysis, normal weight according to BMI was found as an independent protective factor for post-COVID-19 fatigue, and this is consistent with previous literature data. High BMIs and obesity are recognized risk factors for the development of post-COVID-19 symptoms [38,47,48]. A possible explanation for this association may lie in the high levels of inflammation present in obese patients [49], which also constitutes a pathophysiological basis with which to explain the higher risk of mortality for obese patients during the acute stage of infection [50].…”
Section: Discussionmentioning
confidence: 99%
“…The largest was a population-based study involving 456,002 individuals from the United Kingdom at least 4 weeks after COVID-19, where arthralgia was present in 2% to 3% of the patients [72]. In 10 other studies, including 9756 patients overall, a prevalence of joint pain ranging from 10% to 19% was described [35,38,40,41,45,46,51,58,69,73], while 11 studies assessing post-COVID-19 symptoms in 28,303 patients showed higher figures, between 20% and 29% [28,34,42,43,47,49,64,66,71,75,76]. Most of these patients were contributed by Wang et al [71].…”
Section: Joint Pain In Post-covid-19 Patientsmentioning
confidence: 99%